Pengaruh Perubahan Mata Uang Fungsional dan Transaksi atas Mata Uang Asing Terhadap Laporan Keuangan PT Dianta Mitra Fairindo Internasional (International Forum of Researchers and Lecturers, 2024)
Accounting pays close attention to aspects of foreign currency transactions and adjustments to the functional currency that impact financial statements. PSAK 10 is the main guideline in regulating changes in foreign exchange rates and affecting businesses. A good understanding of PSAK 10, functional currency, and foreign currency transactions is crucial for business entities, especially those operating in a foreign currency economic environment. The case study used in this research is descriptive qualitative with literature review method. Research that characterizes research subjects based on emerging facts is known as descriptive qualitative research. The results of the research on the case study of PT Dianta Mitrafairindo Internasional highlighted the significant role of foreign exchange transactions in the company's operations, with management seriously implementing proper accounting processes, dealing with foreign exchange differences, and recording them thoroughly. Despite a loss in 2018, the company managed to record a profit in 2019, demonstrating its seriousness and commitment in managing foreign exchange risks. Overall, PT Dianta Mitrafairindo Internasional demonstrated accuracy, vigilance, and a strong commitment to foreign exchange-related accounting aspects in the context of its global business.